1982
DOI: 10.1099/00221287-128-6-1371
|View full text |Cite
|
Sign up to set email alerts
|

Purification of Chlamydia trachomatis Lymphogranuloma Venereum Elementary Bodies and their Interaction with HeLa Cells

Abstract: A procedure has been developed to yield infectious elementary bodies of the lymphogranuloma venereum strains LGV 434 and 404 of Chlamydia trachomatis, labelled during intracellular growth in HeLa 229 cells. The final preparation, obtained after velocity sedimentation of a polycarbonate membrane-filtered sample through a sucrose gradient, is free of host proteins and, more importantly, of chlamydia1 reticulate bodies. Using such purified preparations, it was found that the association of LGV 434 elementary bodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 13 publications
1
46
0
Order By: Relevance
“…In three separate experiments adherence of the [35S]methionine/[35S]cysteine-labelled L1 C. trachomatis exposed to 1 pg trypsin per 10 pg EB protein for 60 rnin at 37 "C was inhibited by more than 95% when the assays were done at 4°C (data not shown). No inhibition was detected when the adherence assays were done at 37 "C, confirming results with the L2 serovar (Bose & Paul, 1982;Hackstadt & Caldwell, 1985;Su et al, 1988). A double-reciprocal plot of the data obtained at 4 "C with multiple inputs of untreated and trypsin-treated Ll revealed that, in addition to the decrease in V, the apparent K , of adherence by treated EB was 100-fold higher (data not shown).…”
Section: Heat-labile Trypsin-sensitive Chlamydia1 Adhesinsupporting
confidence: 69%
See 2 more Smart Citations
“…In three separate experiments adherence of the [35S]methionine/[35S]cysteine-labelled L1 C. trachomatis exposed to 1 pg trypsin per 10 pg EB protein for 60 rnin at 37 "C was inhibited by more than 95% when the assays were done at 4°C (data not shown). No inhibition was detected when the adherence assays were done at 37 "C, confirming results with the L2 serovar (Bose & Paul, 1982;Hackstadt & Caldwell, 1985;Su et al, 1988). A double-reciprocal plot of the data obtained at 4 "C with multiple inputs of untreated and trypsin-treated Ll revealed that, in addition to the decrease in V, the apparent K , of adherence by treated EB was 100-fold higher (data not shown).…”
Section: Heat-labile Trypsin-sensitive Chlamydia1 Adhesinsupporting
confidence: 69%
“…In our previous studies on the adherence characteristics of C. trachomatis to monolayer cultures of HeLa, McCoy and CHO cells and the glycosylation-defective mutant cell lines of CHO (Bose & Paul, 1982;Bose et al, 1983;Bose & Goswami, 1986a, 6) we utilized metabolically radioactively labelled, highly purified preparations of chlamydial EB. Whenever possible, the data obtained with radioactive EB were confirmed by infectivity determinations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We had previously reported that the adherence of two LGV serovars, 434(L2) and 404(L3), to HeLa 229 was unaffected by WGA (Bose & Paul, 1982), while that of UW-31(K) was enhanced in the absence of the stimulator of adherence, DEAE-dextran (Bose et al, 1983). Data summarized in Table 1 show that the adherence of LGV440 grown in HeLa cells was stimulated by WGA.…”
Section: General Characteristics Of Chlamydia1 Adherencementioning
confidence: 99%
“…For labelling with [5,6-3H]uridine (25 yCi ml-' ; 925 kBq ml-l), regular chlamydial growth medium was used. Reticulate body-free EBs were obtained by velocity sedimentation of filtered samples through a linear 10 to 40% sucrose gradient (Bose & Paul, 1982). After concentration by sedimentation of the EB-containing fractions, samples were quick-frozen and stored at -80 "C.…”
Section: Introductionmentioning
confidence: 99%